Patient characteristics in a return to work programme for common mental disorders: a cross-sectional study - Mattias Victor; Bjørn Lau; Torleif Ruud (BMC, 2016)
Abstract Background Mental health problems are a growing cause of sickness absence. There are programmes in many countries to facilitate return to work (RTW) after sickness absence. In Norway, there has been some controversy about patients on sick-leave being prioritized over other patient groups, such as those with more severe diagnoses. However, it is not clear whether patients in RTW programmes actually do differ from patients in regular services. Methods This study compared 270 patients treated in an RTW outpatient clinic and 86 patients treated in a regular outpatient clinic, both in specialized mental health care, on patient characteristics, history of treatment and mental health status. Analyses of differences between groups were done by ANOVA tests, chi-square test and logistic regression. Results Patients in the RTW clinic had lower scores on the Clinical Outcomes in Routine Evaluation Outcome Measure (CORE-OM). There was no difference in health-related quality of life. RTW patients were somewhat older and more likely to live in relationships and have children, and they had higher incomes. Work participation, previous psychiatric hospitalization and present diagnosis contributed uniquely to an explanation of which patients were included in the respective clinics. The RTW clinic seems to reach its intended target group. Almost all of the patients in this group participated in the work arena, and their psychopathologies were clearly dominated by common mental disorders. Most RTW patients' general practitioners had followed them fairly closely in the year before referral, suggesting previous attempts at treatment in primary care settings. Conclusions Relative to outpatients in a specialized mental health care setting, RTW patients had lower symptoms, but still in the same moderate range of severity. They suffered the same reduction in quality of life. Almost all of the RTW patients were diagnosed with illnesses that can be treated effectively, about half of them had recurring mental health problems and many of them had been treated in primary care settings before referral. These findings indicate that this group has significant health problems that can benefit from treatment in specialized health care settings.